2022
DOI: 10.1002/pc.26992
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation on compression after impact behavior of hygrothermal aged CFRP laminates

Abstract: In the paper, a detailed experimental and numerical investigation of compression after impact (CAI) behavior of hygrothermal aged T300 985LV carbon/ epoxy composites is presented. Rectangular fabric laminates are damaged by low-velocity impact, and moisture absorption conditioning is carried out. The moisture absorption curves agree with Fick's law, with a moisture equilibrium rate of 0.84% at 1392 h. Then, CAI experiments are carried out on moisture saturated specimens at different temperatures. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The greater the interfacial interaction, the more energy is absorbed since energy can be transmitted from the polymer to the fiber across the interface more easily. [37] The WCF/CuO/BPA epoxy resin composite, which was created with eight seeding cycles, 60 mM CuO concentration, and 12 h of treatment, grew the most CuO F I G U R E 6 Variation of absorbed impact energy of samples as a function of time F I G U R E 7 Investigation of load-deflection response of composites under impact loading nanostructures and, as a result, absorbed the most impact energy, 74.8% better than the bare WCF/BPA epoxy resin composite. Additionally, the time taken to failure was increased by 166% in comparison to the bare WCF/BPA epoxy composites as shown in the Figure 6.…”
Section: Energy Vs Time Response Of Impacted Samplesmentioning
confidence: 99%
“…The greater the interfacial interaction, the more energy is absorbed since energy can be transmitted from the polymer to the fiber across the interface more easily. [37] The WCF/CuO/BPA epoxy resin composite, which was created with eight seeding cycles, 60 mM CuO concentration, and 12 h of treatment, grew the most CuO F I G U R E 6 Variation of absorbed impact energy of samples as a function of time F I G U R E 7 Investigation of load-deflection response of composites under impact loading nanostructures and, as a result, absorbed the most impact energy, 74.8% better than the bare WCF/BPA epoxy resin composite. Additionally, the time taken to failure was increased by 166% in comparison to the bare WCF/BPA epoxy composites as shown in the Figure 6.…”
Section: Energy Vs Time Response Of Impacted Samplesmentioning
confidence: 99%
“…Furthermore, CFRP demonstrates greater resistance to corrosion, fatigue, and creep failure compared to other FRP materials. [5][6][7] In China, the market for CFRP in structural reinforcement is experiencing rapid growth, with an annual increase of over 25%. In 2021, the demand for CFRP in the construction reinforcement sector reached 3846 tons, accounting for 4.5% of the total demand.…”
Section: Introductionmentioning
confidence: 99%
“…When the interlayer cracks caused by impact and the initial delamination defects merge in the width direction of the laminate, the CAI strength of the laminate decreases more obviously. Huang et al [ 9 ] investigated the effect of hygrothermal environments on the compression after impact of polymer composites. The results indicated that the CAI strength of 85 RH% hygroscopic saturated laminates is decreased by approximately 12% at 85°C and 17% at 128°C.…”
Section: Introductionmentioning
confidence: 99%
“…When the interlayer cracks caused by impact and the initial delamination defects merge in the width direction of the laminate, the CAI strength of the laminate decreases more obviously. Huang et al [9] investigated the effect of hygrothermal environments on the compression after impact of polymer composites. The results indicated that the CAI strength of 85 RH % hygroscopic saturated laminates is decreased by approximately 12% at 85 C and 17% at 128 C. Although there are many reports on the CAI properties of composites, there are relatively few reports on the influence of matrix-fiber interface on the CAI properties of composites, and there is also a lack of in-depth analysis of the physical and chemical state of fiber surface and the influence of interfacial properties on the CAI properties of composites from a microscopic perspective.…”
mentioning
confidence: 99%